High speed X-ray computed tomography for plant-site analysis of pebble phosphate. (January 2019) - Puvvada, S.; Lin, C.L.; Miller, J.D.
Highlights: HSXCT for quantitative mineral analysis of pebble phosphate. Statistical significance of the HSXCT data. Comparison of the HSXCT results with chemical analysis. Analysis rate of as much as 1 kg/min for pebble phosphate. Abstract: The increase in demand for phosphate by agriculture and allied industries has led to an increase in production by mining and processing operations. According to an estimate by the U.S. Geological Survey, phosphate production will increase from 223 million tons in 2015 to an expected 255 million tons in 2019 (Ober, 2018 ). With the reduced availability of high quality resources, the phosphate industry faces a challenge to meet the ever-increasing demand. For effective utilization of existing pebble phosphate reserves, detailed particle characterization at the plant site should be useful. In this regard, high speed X-ray computed tomography (HSXCT) is being considered to achieve improved processing efficiency to meet the growing industrial demands. The current paper focuses on the demonstration and development of the HSXCT technique for plant-site characterization of the pebble phosphate resources from Florida operations. The study involves high and low MgO pebble phosphate samples obtained from Mosaic's South Pasture and Four Corners operations. The appropriate sample preparation, operating conditions and procedures for HSXCT analysis with the VoluMax 800 system were established. Based on scanning of different sample amounts, satisfactory analysis of pebble phosphate samples has been demonstrated to be possible at a maximum scanning rate of 1 kg/min. The HSXCT data provides mineralogical and liberation analyses for quartz, dolomite and francolite with good reproducibility and good correspondence to the chemical analyses. For example, the mineral composition of each particle in a one kg sample (∼40, 000 particles) can be determined in five minutes, while liberation analysis may take 15 min. Further, the statistical significance of volume grade distribution results from HSXCT analyses was assessed based on scans of replicate samples.